The Integration of Vocational and Soft Skills Education for Santri at Miftahul Ulum Islamic Boarding School, Bangunsirna - Dodi Suhendi; Abdus Salam Dz; Abdul Karim; Ahmad Mujahidin (Program Pascasarjana, Universitas Islam Bunga Bangsa Cirebon, 2025)
Educational transformation in the Education 5.0 era requires Islamic boarding schools to not only strengthen the spiritual dimension but also systematically integrate vocational education and soft skills development within the framework of Islamic educational management. However, studies that position the integration of vocational education and soft skills as a structured managerial strategy are still limited. This study aims to analyze the design, implementation, and control of the integration of vocational education and soft skills at the Miftahul Ulum Bangunsirna Islamic Boarding School. The study used a qualitative approach with a case study design, involving the boarding school leadership, educators, program managers, and students as key informants. Data were collected through in-depth interviews, participant observation, and documentation studies, then analyzed using thematic analysis with data validity maintained through triangulation. The results show that the integration of vocational education and soft skills is not incidental, but is built through coordinated managerial practices, including a competency-based curriculum, collaborative human resource management, and the management of the boarding school's institutional culture as a hidden curriculum. Vocational education is positioned as an inherent part of the Islamic educational mission to actualize the values ​​of knowledge, charity, and morals in the lives of students. This study contributes by formulating a humanistic-integrative Islamic educational management pattern as an empirical description of managerial practices, as well as providing practical references for managing Islamic boarding schools in responding to the demands of contemporary education and the world of work.